Dorsal Anterior Cingulate, Medial Superior Frontal Cortex, and Anterior Insula Show Performance Reporting-Related Late Task Control Signals. (13th March 2016) - Neta, Maital; Nelson, Steven M.; Petersen, Steven E.
Abstract: The cingulo-opercular network (including the dorsal anterior cingulate and bilateral anterior insula) shows 3 distinct task-control signals across a wide variety of tasks, including trial-related signals that appear to come online at or near the end of the trial. Previous work suggests that there are separable responses in this network for errors and ambiguity, implicating multiple types of processing units within these regions. Using a unique paradigm, we directly show that these separable responses withhold activity to the end of the trial, in the service of reporting performance back into the task set. Participants performed a slow reveal task where images were presented behind a black mask which was gradually degraded, and they pressed a button when they could recognize the object that was being revealed. A behavioral pilot was used to identify ambiguous stimuli. We found interactive effects of accuracy and ambiguity, which suggests that these regions are computing and utilizing information, at one time, about both types of performance indices. Importantly, we showed a relationship between cingulo-opercular activity and behavioral performance, suggesting a role for these regions in performance reporting, per se. We discuss these results in the context of task control.